PROJECT-BASED LEARNING ON THE DEVELOPMENT OF TEACHING MEDIA BASED ON INFORMATICS AND COMMUNICATIONS (ICT): GOOGLE SITE FOR ENGLISH TEACHERS MGMP RAYON 5 CITY OF JAMBI - Wira Pratama, Arya; Mahmudah, Khotimah; Fitria, Wahyuni; Rozal, Edi; Sastra Sumardi, Mayang; Putri, Rahmadani; Nirwana, Iin; Ramdayeni Sakunti, Sri (LPPM Univ. Ibn Khaldun Bogor, 2022)
Google site is one of the media that can be used in distance learning. This media can be integrated with a website to facilitate the process of distributing materials and assignments to students. This community service activity uses the Project-based Learning method aimed at English teachers at MGMP Rayon 5 Jambi City where teachers are given work projects to make technology-based teaching materials through Google-site and then integrated through the teacher's account at